Effect of cellular products of potential probiotic bacteria on the immune response of Labeo rohita and susceptibility to Aeromonas hydrophila infection. Issue 2 (October 2015) - Giri, Sib Sankar; Sen, Shib Sankar; Chi, Cheng; Kim, Hyoun Joong; Yun, Saekil; Park, Se Chang; Sukumaran, V.
Abstract In the present study, the immunological efficacy of cellular components from the potential probiotic bacteria Bacillus subtilis VSG1, Pseudomonas aeruginosa VSG2, and Lactobacillus plantarum VSG3 was evaluated in Labeo rohita fingerlings. Fish were immunized intraperitoneally with 0.1 mL phosphate-buffer solution (PBS) containing 0.1 mg of any of the following cellular components: intercellular products (ICPs) of VSG1 (BS-ICPs), heat-killed whole cell products of VSG2 (PA-HKWCPs), or ICPs of VSG3 (LP-ICPs). Fish injected with 0.1 mL PBS served as the control. Various immunological parameters, including the expression of immune-related genes, were measured 14 and 21 days post-immunization. The fish were challenged with Aeromonas hydrophila and mortality was recorded up to 21 days post-infection. The results revealed that administration of cellular components significantly increased the activity of serum lysozyme and the alternative complement pathway, phagocytosis, and respiratory bursts throughout the experimental period. Total serum protein, albumin, and globulin levels were significantly higher in experimental groups than in the control up to 14 days post-immunization, and decreased thereafter. With respect to immune-related genes, IL-1β, COX-2, iNOS, and IL-10 were highly (P < 0.05) up-regulated in fish immunized with cellular components, compared to the control. The expression of TNF-α and NF-κB was up-regulated in immunized fish up to 14 days post-immunization. Interestingly, fish immunized with LP-ICPs exhibited a significantly higher post–challenge relative percent survival (83.32%), followed by PA-HKWCPs (66.66%), and BS-ICPs (50%). These results indicate that cellular components of probiotic bacteria can influence immune responses, enhance disease protection, and stimulate immune-related gene expression in rohu. Hence, these cellular components may be useful as adjuvants for vaccines in aquaculture.